2022
DOI: 10.1111/cas.15272
|View full text |Cite
|
Sign up to set email alerts
|

E2F1‐mediated AUF1 upregulation promotes HCC development and enhances drug resistance via stabilization of AKR1B10

Abstract: The AU-rich binding factor 1 (AUF1) is one of the well known adenylate-uridylate-rich element (ARE)-specific RNA-binding proteins (ARE-BPs) for which dysregulation has been reported in various human cancers. However, the involvement of AUF1 in the initiation and progression of hepatocellular carcinoma (HCC) is still elusive. In this study, we aimed at exploring the clinical significance, function, and mechanism of the abnormal expression of AUF1 in HCC. Using a bioinformatics analysis of The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…An increasing number of studies have shown that AKR1B10 elevation is responsible for certain cancers. For example, AKR1B10 is significantly upregulated in cancers of the breast, lungs, and liver, and AKR1B10 overexpression facilitates the malignant phenotypes of these cancers [ 35 38 ]. In this study, we demonstrated that AKR1B10 exhibits a similar expression pattern and tumor-promoting effects in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that AKR1B10 elevation is responsible for certain cancers. For example, AKR1B10 is significantly upregulated in cancers of the breast, lungs, and liver, and AKR1B10 overexpression facilitates the malignant phenotypes of these cancers [ 35 38 ]. In this study, we demonstrated that AKR1B10 exhibits a similar expression pattern and tumor-promoting effects in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic carcinoma (HCC) is a common kind of cancers which seriously hazards human health [ 2 ]. However, increasing researches demonstrate that HCC cells present multiple strategies to achieve drug resistance [ 145 , 146 ]. Accordingly, it is necessary to search effective strategy to treat HCC.…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…HCC is highly heterogeneous and multiple molecular pathways are involved in the development of drug resistance in HCC cells (9). Combining TKIs and immune checkpoint inhibitors (ICIs) is one way to potentially boost effectiveness and minimize treatment resistance in HCC (10).…”
Section: Introductionmentioning
confidence: 99%